Dukungan terhadap Sensor akan Pornografi dalam Kaitannya dengan Third-Person Perception dan Optimistic Bias - Nuti Indrani Alviana; Amarina A. Ariyanto (Fakultas Psikologi Universitas Pancasila, 2012)
Ever since introduced by Davison (1983), third-person perception (TPP) - the tendency of individuals to assume that mass media have greater influence on others than oneself - have been researched in various contexts and situations. Recent research claims that optimistic bias could explain the occurrence of TPP in individuals. The main focus of this research is to examine TPP in the context of pornography. In line with previous findings, result shows that the majority of adults assume that others are more influenced by the negative effects of pornography within mass media. The power of perceptual bias also has a positive correlation with individual support of pornography censorship. However, that result is only observable if it's tested in individuals that are affected by TPP (assumed that others are more influenced by negative mass media effects than oneself). This study did not find significant correlation between optimistic bias and TPP.